Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $a\ne 0$, $b\ne 0$ and $c\ne 0$ such that $a^2+b^2+c^2=1$. Prove that: $$\dfrac{1-3ab}{1-2ac}+\dfrac{1-3bc}{1-2ba}+\dfrac{1-3ca}{1-2cb}\geq 0.$$

My attempt to the solution: We get that $ab +bc+ca$ lies between $-0.5$ and $1$. We can use this. But I don't know how?

share|improve this question
    
How to solve it.?? –  maths lover Jul 8 '13 at 3:49
1  
Equality holds for $a = b = c$. From the constraint, one can show that the denominators are positive. Thus, multiplying with the denominators does not change the direction of the inequality. Is $0$ the global minimum of the left-hand-side? –  Axel Kemper Jul 8 '13 at 7:36
    
It might help to read the constraint as sphere equation and translate it into a substitution $$\begin{aligned} a & = \cos{\varphi} \cos{\alpha}\\ b & = \cos{\varphi} \sin{\alpha} \\ c & = sin{\varphi} \end{aligned}$$. –  Axel Kemper Jul 8 '13 at 12:46
    
can u show how? –  maths lover Jul 13 '13 at 11:00
2  
@mathslover haha where do you get all of these good questions from? –  Ovi Jul 21 '13 at 0:15

1 Answer 1

up vote 1 down vote accepted

I will use the notation $\sum_{cyc} f(x,y,z)$ to mean that the sum is over the so-called cyclic permutations of $(x,y,z)$ (or the even ones if you prefer), so $\sum_{cyc} f(x,y,z):=f(x,y,z)+f(y,z,x)+f(z,x,y)$ (in place of $x,y,z$ there will also be other variables).

Lemma. If $x,y,z\ge 0$ then $\sum_{cyc} (x+y-2z)(z+x)(x+y)\ge 0$.
Proof. We have $\sum_{cyc}(x+z-2y)(z+x)(x+y)$
$=\sum_{cyc}(x^2z+xyz+x^3+x^2y+xz^2+yz^2+x^2z+xyz-2xyz-2y^2z-2x^2y-2xy^2)$
$=\sum_{cyc} x^3-2\sum_{cyc} x^2y+\sum_{cyc} xy^2=\sum_{cyc} x(x-y)^2\ge 0$. $\blacksquare$

Your inequality (using the hypothesis $a^2+b^2+c^2=1$) can be written as $\sum_{cyc}\frac{(a-b)^2+c^2-ab}{(a-c)^2+b^2}\ge 0$.
Let us call $A=(b-c)^2+a^2$ and $B$, $C$ similarly (by cyclically permuting the variables).
The inequality becomes $\sum_{cyc} \frac{C}{B}\ge\sum_{cyc}\frac{ab}{B}$.
Putting $S=a^2+b^2+c^2$ we clearly have $ab=\frac{S-C}{2}$ (and the cyclic ones), so the inequality is equivalent to $3\sum_{cyc}\frac{C}{B}\ge \sum_{cyc}\frac{S}{B}$ or (which is the same) $3\sum_{cyc}\frac{B}{A}\ge \sum_{cyc}\frac{S}{A}$.
We will prove something slightly stronger, namely that $3\sum_{cyc}\frac{B}{A}\ge\sum_{cyc}\frac{A+B+C}{A}$ (this implies your inequality since $A+B+C\ge S$).
Now observe that $A-B=2c(a-b)\le (a-b)^2+c^2=C$ (and by symmetry $B-C\le A$, $C-A\le B$), so that $A,B,C$ satisfy the triangle inequalities $A\le B+C$, $B\le C+A$, $C\le A+B$.
We can thus perform the substitution $A=y+z,B=z+x,C=x+y$ with $x,y,z\ge 0$ (if you didn't know this fact, check it!).
So we are left to prove that $\sum_{cyc}\frac{3(z+x)-2(x+y+z)}{y+z}\ge 0$, which is the Lemma (upon clearing the positive denominators).

share|improve this answer
    
Where does this problem come from? –  Mizar Dec 25 '13 at 18:24

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.